PEMBELAJARAN BAHASA ARAB DI IAIN SULTHAN THAHA SAIFUDDIN JAMBI: ARABIC LEARNING IN SULTAN THAHA SAIFUDDIN IAIN JAMBI - Yusraini Yusraini; Yogia Prihartini (Balai Penelitian dan Pengembangan Agama Jakarta, 2014)
Educational experts recognize that learning conditions affect student achievement. The same applies for Arabic learning. Despites the important effects which learning conditions have on student achievement, Arabic learning conditions are still the rare subject to research. It is therefore important to know current Arabic learning conditions in order to improve the results of Arabic learning. This article summarizes the findings of a research on Arabic learning conditions in Sultan Thaha Saifuddin IAIN (State Institute for Islamic Studies) Jambi. Components of learning conditions examined include the objectives and characteristics of the subject (in this case, Arabic learning), constraints to the Arabic learning, and student characteristics. This research found among others that the short of learning time, Arabic learning environments, limited Arabic learning facilities, the high ratio of student numbers to class capacity, and less motivated students are among the factors that create constraints to Arabic learning in the college. Key Words: Learning conditions, Arabic, learning constraints, Sultan Thaha Saifuddin IAIN, Jambi. Para ahli pendidikan memandang, bahwa kondisi pembelajaran mempengaruhi prestasi siswa. Hal yang sama juga terjadi dalam pembelajaran Bahasa Arab. Meskipun demikian, kondisi pembelajaran Bahasa Arab jarang menjadi subjek pembahasan. Oleh karena itu, untuk meningkatkan kualitas pembelajaran Bahasa Arab, diperlukan pengetahuan mengenai kondisi pembelajarannya. Tulisan ini menyajikan hasil penelitian terhadap kondisi pembelajaran Bahasa Arab di IAIN Sulthan Thaha Saifuddin (STS) Jambi. Elemen-elemen kondisi pembelajaran yang dijelaskan adalah tujuan pembelajaran, karakteristik pembelajaran Bahasa Arab, kendala-kendala pembelajaran dan karakteristik siswa. Penelitian ini menemukan, bahwa kurangnya waktu, lingkungan pembelajaran, keterbatasan fasilitas, rasio jumlah mahasiswa terhadap kapasitas kelas, dan kurangnya motivasi mahasiswa dalam belajar Bahasa Arab, adalah beberapa faktor yang menjadi kendala pembelajaran Bahasa Arab di perguruan tinggi. Kata Kunci: Bahasa Arab, kondisi pembelajaran, IAIN Sultan Thaha Saifuddin, Jambi.